2022
DOI: 10.3390/polym14071331
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites of Polyhydroxyurethane with POSS Microdomains: Synthesis via Non-Isocyanate Approach, Morphologies and Reprocessing Properties

Abstract: In this contribution, we reported the synthesis of a novel trifunctional POSS cyclic carbonate [POSS-3(5CC)]. With a difunctional five-member cyclic carbonate and a trifunctional polyetheramine as the precursor, the nanocomposites of polyhydroxyurethane (PHU) with POSS were synthesized. Transmission electron microscopy (TEM) showed that the nanocomposites of PHUs with POSS were microphase-separated; the spherical POSS microdomains via POSS-POSS interactions were generated with the size of 20~40 nm in diameter.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Thus, the presence of f-BN appears to increase not only the cross-link density but also the homogeneity of the network structure. Similar shifts in T g have been reported in PHU filled with CNTs [ 20 ], polyhedral oligomeric silsesquioxanes [ 16 ], and graphenated ceramic fillers [ 24 ].…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Thus, the presence of f-BN appears to increase not only the cross-link density but also the homogeneity of the network structure. Similar shifts in T g have been reported in PHU filled with CNTs [ 20 ], polyhedral oligomeric silsesquioxanes [ 16 ], and graphenated ceramic fillers [ 24 ].…”
Section: Resultssupporting
confidence: 76%
“…Studies of PHU nanocomposites are still scarce, but they have already shown improved thermal and mechanical properties, adhesion performances, and shape memory [ 10 ]. Although the main used fillers for PHU nanocomposites have been zero dimensional nanoparticles (silica [ 12 , 13 , 14 ], polyhedral oligomeric silsesquioxanes [ 15 , 16 ], ZnO [ 17 ], and Fe 3 O 4 [ 18 ]), both one-dimensional nanomaterials, (particularly carbon nanotubes [ 19 , 20 ] and nanocellulose [ 21 ]) and two-dimensional nanomaterials (nanoclay [ 22 , 23 ] and graphene [ 24 , 25 ]), have also been studied. Here, we investigate the incorporation of functionalized hexagonal boron nitride (f-BN) into PHU to provide high mechanical and thermal properties.…”
Section: Introductionmentioning
confidence: 99%
“…Such features make POSS an appealing framework for fabricating vitrimers with high incorporation of inorganic fillers, thereby yielding materials that combine dynamicity with stability. However, POSS-based vitrimers have only recently garnered attention as promising platforms for composite CANs. Herein, we report the incorporation of novel β-ketoester-functionalized POSS cages to form nanocomposite vitrimers which, to the best of our knowledge, possess the highest weight percent POSS to date in vitrimer materials. The high degree of POSS cross-linked with various diamines led to vitrimers with tunable viscoelastic flow and glass transition temperatures ( T g ), excellent creep resistance, and high-performance charring capabilities, potentially making these materials promising as HSMs with tailorable shapes.…”
Section: Introductionmentioning
confidence: 99%
“…Each Si atom located at the corners has an R group extending into the external space, which is the main factor that makes the POSS exhibit different functional properties. 25 Since the bond energy of the Si−O bond (445.2 kJ/mol) is larger than that of the C−C bond (350.7 kJ/mol), the C−O bond (359.1 kJ/mol), etc. in the R group, it is more difficult to destroy these Si−O bonds in the cores, which is the main factor that the POSS has a high strength macroscopically.…”
mentioning
confidence: 99%
“…Polyhedral oligomeric silsesquioxane (POSS) is a kind of polyhedron oligomeric sesquisiloxane nanostructure hybrid system that has a hexahedron core composed of Si–O–Si, in which each corner contains a Si atom and each surface is composed of a Si–O–Si octahedron ring, which has a strong structural symmetry. Each Si atom located at the corners has an R group extending into the external space, which is the main factor that makes the POSS exhibit different functional properties . Since the bond energy of the Si–O bond (445.2 kJ/mol) is larger than that of the C–C bond (350.7 kJ/mol), the C–O bond (359.1 kJ/mol), etc.…”
mentioning
confidence: 99%